2004
DOI: 10.1007/s00405-004-0857-2
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase/soluble guanylate cyclase system in human nasal polyps

Abstract: The aim of our study was to analyze the level of expression of the endothelial nitric oxide synthase (eNOS)/soluble guanylate cyclase (sGC) system in nasal polyps and control nasal mucosae. The study was performed in polyps from 15 patients and nasal mucosae from 11 subjects operated on the nasal septum (control group). The expression of endothelial nitric oxide synthase (eNOS) and soluble guanylate cyclase (sGC) was determined in nasal mucosae. Western blot analysis demonstrated that eNOS protein was overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
0
1
Order By: Relevance
“…An increase in oxidative stress and deficient antioxidant mechanisms may also play a role in the pathophysiology of NP (26,27). Several studies have reported increased NOS levels in NP patients (28,29). We also found lower ADMA values in the NP group than in the control group, but there was no statistically significant difference.…”
Section: Discussioncontrasting
confidence: 49%
“…An increase in oxidative stress and deficient antioxidant mechanisms may also play a role in the pathophysiology of NP (26,27). Several studies have reported increased NOS levels in NP patients (28,29). We also found lower ADMA values in the NP group than in the control group, but there was no statistically significant difference.…”
Section: Discussioncontrasting
confidence: 49%